2005
DOI: 10.1002/anie.200500022
|View full text |Cite
|
Sign up to set email alerts
|

Benzene Formation at 70 °C by Coupling of Propylene on Supported Pd Nanoclusters

Abstract: Reactions on supported transition metal clusters have important applications and often display unexpected reactivity when the cluster size is on the nanometer scale.[1] As reliable methods of preparing size-selected supported clusters have been developed, relationships between the preparation method, size, and/or support have become apparent, albeit poorly understood. Metal clusters can be synthesized by using micelle encapsulation, and this method has been further developed to make nanocluster powders support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…As is known, the small particle size as well as the high surface area of the Pd nanoparticles is often unstable at elevated reaction temperatures [13][14][15]. Researchers found that the pore channels of mesoporous supports have the potential ability to inhibit active particles growth and aggregation during reactions [7,16].…”
Section: Introductionmentioning
confidence: 99%
“…As is known, the small particle size as well as the high surface area of the Pd nanoparticles is often unstable at elevated reaction temperatures [13][14][15]. Researchers found that the pore channels of mesoporous supports have the potential ability to inhibit active particles growth and aggregation during reactions [7,16].…”
Section: Introductionmentioning
confidence: 99%
“…This is strongly related to the ability of −NHCO− to act simultaneously as hydrogen‐bond donor and acceptor. These structures include helices, zig‐zags, antiparallel β‐strands, tapes, macrocycles, cryptands, capsules, Janus‐dendrimers, and molecular electrets . Clearly, this ability has been utilized by nature to form three‐dimensional peptide and protein secondary structures .…”
Section: Introductionmentioning
confidence: 99%
“…[12] The presence of multiple secondary amide groups in organic molecules has been provent ob earobustw ay of increasing the propensity for said molecule to self-assemble into reprodu-cible secondary structures.T his is strongly related to the ability of ÀNHCOÀ to act simultaneously as hydrogen-bond donor and acceptor. These structures include helices, [13] zig-zags, [14] antiparallel b-strands, [15] tapes, [16] macrocycles, [17] cryptands, [18] capsules, [19] Janus-dendrimers, [20] and molecular electrets. [21] Clearly,this ability has been utilized by naturet oformthree-dimensional peptide and protein secondary structures.…”
Section: Introductionmentioning
confidence: 99%
“…Pd‐based heterogeneous catalysts have been used in a wide range of important chemical processes including CO oxidation,1, 2 aerobic alcohol oxidation,3 NO x reduction,4 conversions of volatile organic compounds,5, 6 hydrogenation,7–9 and dehydrogenation 10. Recent work has suggested that when the dimensions of the Pd particles are reduced to less than 10 nm the catalysts are extraordinarily active and may exhibit unique properties 11–14. Unfortunately, Pd as well as other metal nanoparticulate catalysts are often unstable with respect to sintering on oxide supports at elevated reaction temperatures and their activity rapidly decays 15–19…”
mentioning
confidence: 99%
“…[10] Recent work has suggested that when the dimensions of the Pd particles are reduced to less than 10 nm the catalysts are extraordinarily active and may exhibit unique properties. [11][12][13][14] Unfortunately, Pd as well as other metal nanoparticulate catalysts are often unstable with respect to sintering on oxide supports at elevated reaction temperatures and their activity rapidly decays. [15][16][17][18][19] To stabilize nanoparticulate metals, unique structures consisting of metal cores surrounded by oxide, carbon, or other metal shells (core/shell) have been created.…”
mentioning
confidence: 99%